Analisis Tiang Pancang dengan Uji Dinamis dan Statis terhadap Kapasitas Ijin Manufaktur - Kurniawan Tanjung, Dian; Zaki, M. (Journal of Comprehensive Science, 2025)
Pile foundation is one of the methods used to increase the carrying capacity of building structures, especially in varying soil conditions. This study aims to analyze the carrying capacity of pile foundation tops using various static formulas, such as Meyerhoff (1956), Poulus & Davis, Schmertmann, Coyle & Castilo, and the Alpha & Lambda Method, and compare them with the results of static testing using the Mazurkiewich & Chin method as well as dynamic testing with the Case Pile Wave Analysis Program (CAPWAP). The research method used includes the collection of primary data from the F2 Building construction project at the X Shoe Factory, which includes Standard Penetration Test (SPT) data, Cone Penetration Test (CPT), piling calendar, and static and dynamic load test results. The results show that the Meyerhoff method with Terzaghi correction NSPT has the closest value to the static and dynamic test results, while the most accurate dynamic formula is the ENR modified formula. In addition, the comparison of the carrying capacity of the pole to the allowable load of the design and manufacturing shows that there is still efficiency that can be done in the selection of the type and dimension of the pole. In conclusion, this study provides insight into the optimal carrying capacity calculation method and cost efficiency in the implementation of pile foundations, which can be a reference in the planning and design of building structures.